2009
DOI: 10.1007/s10059-009-0026-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Homodimerization of Toll-like Receptor 4 by 6-Shogaol

Abstract: Toll-like receptors (TLRs) play a critical role in sensing microbial components and inducing innate immune and inflammatory responses by recognizing invading microbial pathogens. Lipopolysaccharide-induced dimerization of TLR4 is required for the activation of downstream signaling pathways including nuclear factor-kappa B (NF-kappaB). Therefore, TLR4 dimerization may be an early regulatory event in activating ligand-induced signaling pathways and induction of subsequent immune responses. Here, we report bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…Additionally, Ahn et al showed that ginger inhibits homodimerization of TLR4 which suppress its functions [25]. Another study revealed that ginger suppresses expression of inflammatory genes in a NF-κB dependent manner [26]. NF-κB is a main transcription factor down-stream of TLR2 and 4 and participates in the expression of the TLRs [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ahn et al showed that ginger inhibits homodimerization of TLR4 which suppress its functions [25]. Another study revealed that ginger suppresses expression of inflammatory genes in a NF-κB dependent manner [26]. NF-κB is a main transcription factor down-stream of TLR2 and 4 and participates in the expression of the TLRs [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Protein extracts from Ba/F3 cells expressing TLR4 (Flag or GFP-tagged), CD14, MD2 (Flag-tagged), and NF-κB luciferase reporter gene were prepared for immunoprecipitation as described previously 8,11 . Briefly, the samples were immunoprecipitated by an overnight application of mouse-green fluorescent protein (GFP) antibody (Molecular Probes, Eugene, OR, USA).…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…The assays were performed as described previously (17,18). Briefly, RAW264.7 cells were co-transfected with a luciferase plasmid and HSP70-β-gal plasmid as an internal control using SuperFect transfection reagent (Qiagen) according to the manufacturer's instructions.…”
Section: Transfection and Luciferase Assaymentioning
confidence: 99%